Penerapan Model Argumentasi Driven Inquiry ( ADI) Dengan Bantuan PhET Simulation Untuk Melatih Argumentasi Ilmiah Peserta Didik Kelas XI SMA Pada Topik Gas Ideal (IPF: Inovasi Pendidikan Fisika, 2022)
The learning system in the 21st century has a goal that focuses on the ability of students to solve problems and think critically. In the process, this ability needs to be supported by a skill, namely the ability to carry out scientific arguments. The purpose of this study is to describe the implementation of the Argument-Driven-Inquiry learning model in physics learning, the effect of the application of the ADI learning model on students' scientific argumentation abilities and student responses to the application of the ADI learning model. The type of research used is Experimental Design, with a research design of Pretest-Posstest Control Group Design. Data collection methods used are observation, tests and questionnaires. The results of the study showed that ADI's learning was carried out very well. Based on the class category, the ability to argue scientifically in each student has a significant difference where this is reinforced by the gain value. The gain value for the experimental class reached 0.49 (medium category) and the control class only reached 0.17 (low category). The statistical perspective noted that the student's response had three main factors as factors that formed the pattern of students' argumentation, with a cumulative percentage of 69.591%. Keywords: Argument-Driven Inquiry, PhET Simulation, Scientific Argumentation Skills